Acute invasive mucormycosis rhinosinusitis causing multigroup cranial nerve injury and meningitis—A case report - Wang, Tingting; Cao, Duanhua; Han, Jingzhe (Frontiers in Neurology, 2022)
In this study, we report a case of a Rhino-Orbital-Cerebral Mycosis (ROCM) patient with multiple groups of cranial nerve damage as the primary clinical manifestation and confirmed by histopathology and cerebrospinal fluid metagenomic next-generation sequencing (mNGS) technology. Relying on the MRI3D-SPACE technology, we observed the location and extent of the patient's cranial nerve damage. The results suggest that fungal meningoencephalitis caused by mucor may enter the skull retrograde along the cranial nerve perineurium. The patient was admitted to the hospital with a preliminary diagnosis of mucormycosis infection after 1.5 days of mouth deviation. We treated the patient immediately with intravenous amphotericin B liposomes. After 21 days of hospitalization, the patient's clinical symptoms did not improve significantly. The patient was discharged due to financial difficulties and antifungal treatment at home, and his disease stabilized at the 6-month follow-up.